Peran Guru Dalam Penanaman Karakter Religius Bagi Siswa Penyandang Autis - Nur Aisa; Ratna Purwanty; Dewi Puji Rahayu (Musamus Journal of Primary Education, 2021)
The objectives of this study are: (1) to describe the role of teachers in inculcating religious characters for students with autism, (2) to describe the supporting and inhibiting factors for inculcating religious characters for students with autism, (3) to describe the character traits of autistic children. This research was qualitative descriptive research. It was conducted at SLB Negeri Anim Ha Merauke.Techniques and instruments of data collection were through interviews and documentation. The data analysis used source triangulation and member check. The results showed that the teacher’s role in inculcating religious character for students with autism at SLB Negeri Anim Ha Merauke was seen in the teacher’s activities in inculcating religious character in schools through learning activities by providing understanding, teaching good habits, and the teacher became the role model for students. The students are expected to have characters that are obedient to God’s commands, polite, tolerant, friendly, and can interact in their environment. So, the students are accepted by the society.